Inter-Segmental Timing as A Contributing Factor to Knee Loading in Stop-Jump Landings - Cedric Schwartz; Julien Paulus; Jean-Louis Croisier; Laura Delhauteur; Etienne Dubois; Jean-François Kaux (Journal of Sports Science and Medicine, 2026)
Landing tasks are a major contributor to knee injuries in sport. While biomechanical determinants of knee joint loading have already been studied, less attention has been given to the role of inter-segmental timing during sport-specific landings. This study aimed to examine both biomechanical and temporal predictors of knee joint loading during horizontal and vertical phases of stop-jump landings. Thirty-three male volleyball and basketball players performed stop-jump tasks while lower-limb kinematics, kinetics, patellar tendon forces, and anterior tibial shear forces were calculated. Statistical Parametric Mapping and Linear Mixed Models were used to identify phase-specific differences and predictors of knee loading. Inter-segmental timing, quantified as foot-contact delay between body segments, emerged as a significant predictor of knee joint loading across conditions. This finding extends previous work by highlighting inter-segmental timing as an additional factor influencing knee joint loading alongside established biomechanical predictors such as displacement velocity, body mass, and knee range of motion. Horizontal landing phases showed a stiffer strategy compared to vertical phases, with reduced joint range of motion (40–83%) and increased knee valgus. These differences were associated with higher anterior tibial shear (121%) and patellar tendon (156%) forces. These results may be particularly relevant in sport situations where landings are not fully planned and can be altered by external perturbations such as opponents’ deceiving actions.